The mathematical models and function algorithms of automatic control system of dynamic treatment process on underground massive - Pavlysh, V.N.; Lazebnaya, L.A. (Искусственный интеллект, 2014)
The mathematical models of technological process of pneumatic and hydrodynamic treatment on anisotropic underground rock massive, saturated with useful minerals, is considered. The treatment applies as a way of directed changing of massive status for intensification of mineral extraction and its effectiveness depends of quality of parameters control. The structure of the automatic control system and the algorithm of its parameters selection is proposed.